Clinical significance of diabetes likely induced by statins: Evidence from a large population-based cohort. (November 2017) - Corrao, Giovanni; Monzio Compagnoni, Matteo; Rea, Federico; Merlino, Luca; Catapano, Alberico L.; Mancia, Giuseppe
Highlights: Use of statins can both increase new-onset diabetes and decrease CV risk. Several aspects of statin-induced diabetes have not been adequately clarified. Statin-induced diabetes might have a more favorable prognosis than native diabetes. Our study questions the impact of statin-induced diabetes on macrovascular risk. Statin-induced diabetes is not associated with clear increase of macrovascular risk. Abstract: Aim: To provide information on the extent to which type 2 diabetes more likely induced by statins affects the risk of macrovascular complications compared to diabetes unlikely induced by statins. Methods: The 84, 828 residents in the Italian Lombardy Region who were newly treated with statins between 2003 and 2005 were followed from the index statin prescription until 2009 (step-1 follow-up) to identify those starting antidiabetic therapy. The proportion of days of follow-up covered by statins measured adherence with statins. Cohort members who experienced diabetes were 1:3 matched with those who did not developed diabetes for gender, age and previous adherence with statin treatment. The 3321 diabetic - non-diabetic sets, were followed from the initial antidiabetic therapy until 2012 (step-2 follow-up) to estimate the hazard ratio (HR), and 95% Confidence Interval (CI), for macrovascular complications (proportional hazard models) associated with diabetes separately in each category of adherence with statins. Results: During the step-1 follow-up, the risk of new-onset diabetes increased progressively with increasing adherence with statins. During the step-2 follow-up, the risk of macrovascular complications associated with diabetes decreased progressively from 1.70 (1.18–2.44), 1.41 (1.17–1.70), 1.30 (1.07–1.57) until 1.10 (0.40–2.80) as adherence with statins during the step-1 follow-up increased. Conclusions: Type 2 diabetes lost its association with increasing macrovascular risk when previous adherence with statins was very high, and thus the chance of its induction by the drug greater. Statin-dependent type 2 diabetes might be prognostically less adverse than diabetes unlikely induced by statins.